PENINGKATAN HASIL BELAJAR MENULIS NARRATIVE TEXT MELALUI METODE CONTEXTUAL TEACHING LEARNING (CTL) KELAS IX A SMP NEGERI 4 PRACIMANTORO - Marlina Tri Handari (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2023)
This is a Classroom Action Research (CAR) study. The research subjects are 27 students in Grade IX-A at State Junior High School 4 Pracimantoro. Data collection techniques include written tests, observation, and documentation. The research procedure is conducted through two cycles, each consisting of planning, implementation, observation, and reflection. CTL consist of 4 steps, they are invitation, eksploration, explaining and solution also action taking. Invitation consists of material explanation and discussion. Exploration consists of making a group, share a series pictures to each group about narrative text, observation also discussion and arrange a series pictures. Explanation and solution consists presentation of the group discussion result after doing observation and analysis then other group give respond also take summary from the discussion. Action taking consist expressing opinion, asking and answer and give suggestion that have relation with solving problem. The research results were able to answer the research question, which was to improve the narrative writing skills in each cycle. In the initial stage, the class had an average score of 50.59 with a mastery percentage of 7.41% (2 students). In Cycle I, meeting I, the average score improved to 61.33 with a mastery percentage of 25.93% (7 students). In Cycle I, meeting II, the average score further increased to 68.92 with a mastery percentage of 44.44% (12 students). In Cycle II, meeting I, the class achieved an average score of 74.15 with a mastery percentage of 70.37% (19 students), while in Cycle II, meeting II, the average score was 77.41 with a mastery percentage of 88.89% (24 students).